Criminological Review of the Crime of Personal Data Theft on Online Loans: Tinjauan Kriminologi Terhadap Kejahatan Pencurian Data Pribadi Pada Pinjaman Online - Salomo , Juan Caesar; Utari, Indah Sri (Annual Review of Legal Studies, 2024)
The rise of online lending platforms has facilitated easy access to financial assistance, but it has also ushered in a new wave of criminal activity: the theft of personal data for fraudulent purposes. This paper provides a criminological review of the crime of personal data theft on online loans. It explores the underlying factors driving individuals to engage in this criminal behavior, analyzes the protective measures available to potential victims, and examines the efficacy of criminal sanctions in deterring such offenses. By applying rational choice theory, cause-and-effect theory, and an integrated perspective, the research sheds light on the complex dynamics of this emerging form of cybercrime. Moreover, it highlights the urgent need for enhanced public awareness and proactive law enforcement measures to combat the proliferation of personal data theft in the realm of online lending.